2018
DOI: 10.1302/0301-620x.100b8.bjj-2017-1297.r1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse hybrid total hip arthroplasty

Abstract: This is the largest reported study into reverse hybrid THA and it confirms successful outcomes, irrespective of age, gender, head size and surgeon grade. Cite this article: Bone Joint J 2018;100-B:1010-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In such cases, the cemented arthroplasty advocates recommend a hybrid surgery that produces a better functional effect than the screw-cup system (cemented acetabulum, stem fixed with no cement) [12,13]. Similarly to the findings of other authors, our study confirms that BMI, gender, type of incision and cutaneous suture have no impact on the functional outcome and incidence of complications following the hip arthroplasty operation [14]. Moreover, we demonstrate that there is a high negative correlation between functional outcomes and age, which is not reflected in the literature [15].…”
Section: Discussionsupporting
confidence: 87%
“…In such cases, the cemented arthroplasty advocates recommend a hybrid surgery that produces a better functional effect than the screw-cup system (cemented acetabulum, stem fixed with no cement) [12,13]. Similarly to the findings of other authors, our study confirms that BMI, gender, type of incision and cutaneous suture have no impact on the functional outcome and incidence of complications following the hip arthroplasty operation [14]. Moreover, we demonstrate that there is a high negative correlation between functional outcomes and age, which is not reflected in the literature [15].…”
Section: Discussionsupporting
confidence: 87%
“…One author provided additional unpublished data in the form of net survival estimates. 27 Reidy et al reported survival estimates, but no CIs. 13 Net survival estimates and corresponding CIs were thus extracted from three studies at 5 years and one study at 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Additional data provided by the author indicate that they found no evidence of a difference in implant survival according to surgeon grade (Trainee: 98.1%; 95% CI 95.9 to 99.1; Consultant: 96.7%; 95% CI 94.7 to 97.9). 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining published literature on this topic is limited to a small number of observational studies, none of which have reported a negative association between THAs performed by trainees and implant failure. [18][19][20][21] The relationship between surgical experience and the dislocation of THAs has been the focus of previous investigation. Individual cohort studies [22][23][24] and meta-analyses have drawn contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%